Non-Invasive Evaluation of Liver Fibrosis Using Real-Time Elastography and Comparison of Intercostal and Subcostal Approaches. - Uslu, Abdulaziz; Batur, Abdussamet; Bıyık, Murat; Acıkgozoglu, Saim (European Journal of General Medicine, 2015)
In patients with chronic liver diseases, the identification of significant fibrosis is of special interest, because the presence of fibrosis is an important parameter for the estimation prognosis, for survelliance and for treatment decisions in patients with Chronic Liver Diseases. Although percutaneous liver biopsy is the gold standart method for assessing liver fibrosis, it has some limitations including its invasive nature, inconvenience, sampling errors, inadequate specimen size and interobserver variability in pathology interpretation. Therefore many studies have focused on the evaluation of noninvasive methods for the assessment of liver fibrosis stage. One of these methods is real time elastography which measures tissue elasticity. In the present study, we assessed intercostal and subcostal measurement methods to discriminate between normal and fibrotic liver .